Mediamorfosis Radar Bandung - Youris Marcelina; Khoiruddin Muchtar; Imron Rosyidi (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
The transformation of human communication will continue as time goes by. The discovery of the adoption of electricity, computer technology, and the birth of digital languages contributed to the transformation of mass media that occurred in the era of digitalization. This study aims to determine the media transformation carried out by Radar Bandung based on the concept of Mediamorfosis initiated by Roger Fidler. The research examines the coevolution process, convergence, and complexity of the development of print media to online media on Radar Bandung. The method used in this research is a descriptive study with a qualitative approach. The results showed that the Radar Bandung coevolution process had been approved and implemented digital language to obtain a new business diversification and two online media radarbandung.id and bandung.pojoksatu.com. The Radar Bandung convergence process produces two types of convergence, namely a form of technological convergence and journalistic convergence. The complexity that arises is the prediction of print media death and the delayed adoption of QRcode scan technology. However, the existing difficulties do not make it fatal but an opportunity in the future.